Power of Hypoperfusion in Predicting Recurrent Transient Ischemic Attacks: Protocol of a Prospective Cohort Study - Wang, Yue; Liang, Huazheng; Jin, Lingjing; Wang, Shaoshi (Frontiers in Human Neuroscience, 2021)
Background：Transient Ischemic Attack (TIA) has a high incidence of recurrent vascular events. Hypoperfusion is one of the factors that are closely correlated with 7-day recurrence of TIA. The present study aimed to evaluate the power of hypoperfusion shown on MR perfusion in predicting the incidence of 7-day recurrence of ischemic events after TIA. Methods/design：REATTACK is a prospective, multi-centered, cohort study on the correlation between magnetic resonance (MR) perfusion and TIA recurrence. Ninety patients aged ≥ 18 years with a recent (< 7 days after onset) clinical TIA will be continuously included. All patients will undergo diffusion-weighted imaging (DWI) and perfusion-weighted imaging (PWI) assessment within 24 hours after the onset of TIA. Subjects will then be divided into a PWI positive group and a PWI negative group according to the time to maximum of the residue function (Tmax). PWI will be repeated after 7 days and 3 months, respectively. The primary clinical outcome will be the recurrence of TIA within 7 days after the onset of TIA. The secondary outcomes will be the 3-month recurrence of TIA and the modified ranking scale (mRS) score. Chi-square test will be performed to compare the difference in the incidence of recurrent TIA between the two groups, and Rank Sum test in the mRS score. Multivariate logistic regression will be simultaneously performed to analyze the risk factors for recurrence of TIA. Discussion：The results of the present study will confirm whether abnormal Tmax helps identify TIA patients with high risks of recurrent ischemic events. This would largely improve the prognosis of TIA patients. Trial registration: www.chictr.org.cn, registration number: ChiCTR2000031863, registered on 12 April 2020.